2015
DOI: 10.1179/1751584x15y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of BN and B4C particulates on wear and corrosion resistance of electroplated nickel matrix composite coatings

Abstract: Electrodeposition of nickel-boron nitride-boron carbide (Ni-BN-B 4 C) composites was carried out from a Watt's solution containing 50 and 10 g L 21 of dispersed boron nitride and boron carbide particles respectively. The corrosion behaviour for both Ni and Ni-BN-B 4 C deposits was evaluated by polarisation curves in a 3?5% NaCl solution at room temperature. Wear resistance of the composites was also studied using pin on disc technique. Scanning electron microscopy was extensively used to understand the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The corrosion current density, also known as (Icorr) can be determined by locating the point where the linear portions of the anodic and cathodic Tafel curves intersect. In this equation, M represents the atomic mass, V represents the number of electrons lost in the oxidation reaction, D represents the density, and A represents the exposed area of the sample [20].…”
Section: Corrosion Testmentioning
confidence: 99%
“…The corrosion current density, also known as (Icorr) can be determined by locating the point where the linear portions of the anodic and cathodic Tafel curves intersect. In this equation, M represents the atomic mass, V represents the number of electrons lost in the oxidation reaction, D represents the density, and A represents the exposed area of the sample [20].…”
Section: Corrosion Testmentioning
confidence: 99%
“…Paydar et al studied the wear and corrosion resistance of the electroplated nickel matrix composites through the boron nitride and boron carbide deposition. The BN particle concentration in the deposition has maximized the corrosion resistance than the bare nickel coating [14]. Aluminium 7075 composites having 3% BN and 6% zirconium dioxide showed the higher mechanical strength with decent wear resistance.…”
Section: Introductionmentioning
confidence: 98%
“…From the literature survey, it is concluded that the various experimentations conducted for both single and hybrid reinforced Al 6061 matrix composites through stir casting method results in producing optimal engineering properties. But recently, there is less attention focussed on incorporating boron nitride material as reinforcement in the Aluminium 6061 matrix composites through the stir casting method, as this material possesses better mechanical, wear, thermal and corrosion resistance [13,14]. This paper aims to incite the mechanical, wear and corrosion behaviour of the stir casted Al 6061 hybrid composites with boron nitride, aluminium oxide and graphite as the reinforcement and make them superior than the bare Al 6061 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…But, it increases the hardness and selflubricating property. Further, Ni-based B 4 C is not affected by the acids and alkaline used during electroplating [29]. The corrosion resistance and hardness of the AZ31 Mg alloy could be increased by Ni-B 4 C composite coating and can be further improved by optimising electroplating parameters.…”
Section: Introductionmentioning
confidence: 99%